Da desigualdade Ã diferença: um caso grave de deslocamento? - Phillips, Anne (Revista Brasileira de Ciência Política, 2012)
Resumo Neste texto, a cientista política inglesa Anne Philips situa o debate entre Iris Marion Young e Nancy Fraser, publicado neste número. Segundo a análise aqui presente, ambas levam em consideração o econômico e o cultural em suas análises. Young, porém, não seria capaz de incorporar algumas formas de exploração e marginalização em seu continuum de formas de opressão organizado a partir da noção de diferença. Fraser, por sua vez, integra as duas categorias sem que consiga evitar uma valorização da distribuição que a leva a medir o valor do reconhecimento pela promoção ou não da distribuição. Valorizando aspectos das duas análises, o texto considera que o ponto central não é a existência de categorias analíticas distintas, mas o entendimento de que não existem de modo independente, presente nas duas autoras. As diferenças seriam, sobretudo, que Fraser destaca os conflitos entre as dimensões econômica e cultural, enquanto Young opta por ressaltas sua interconexão. Palavras-chave: Nancy Fraser; Iris Marion Young; identidades; exclusão. Abstract In this article, the British political scientist Anne Philips situates the debate between Iris Marion Young and Nancy Fraser, published in this number. According to her analysis, both, Young and Fraser, take into consideration the economic and the cultural in their analyses. Young, however, would not be capable of incorporating some forms of exploitation and marginalization in her continuum of forms of oppression organized in base of the notion of difference. Fraser, in her turn, proceeds to an integration of the two categories, but does not avoid an overvaluation of distribution, what leads her to measure the value of recognition in function of its capacity of promoting, or not, the distribution. Valuating aspects of the two analyses, the text considers that the central point is not the existence of distinct analytical categories, but the understanding that they do not exist independently, an understanding that is common to both authors. The differences would be, above all, that Fraser emphasizes the conflicts between the economic and cultural dimensions, while Young’s option is in the sense of giving prominence to their interconnection. Keywords: Nancy Fraser; Iris Marion Young; identities; exclusion.